Which chemicals drive biological effects in wastewater and recycled water? - Tang, J.; Busetti, Francesco; Charrois, Jeffrey; Escher, B. (IWA Publishing, 2014)
Removal of organic micropollutants from wastewater during secondary treatment followed by reverse osmosis and UV disinfection was evaluated by a combination of four in-vitro cell-based bioassays and chemical analysis of 299 organic compounds. Concentrations detected in recycled water were below the Australian Guidelines for Water Recycling. Thus the detected chemicals were considered not to pose any health risk. The detected pesticides in the wastewater treatment plant effluent and partially advanced treated water explained all observed effects on photosynthesis inhibition. In contrast, mixture toxicity experiments with designed mixtures containing all detected chemicals at their measured concentrations demonstrated that the known chemicals explained less than 3% of the observed cytotoxicity and less than 1% of the oxidative stress response. Pesticides followed by pharmaceuticals and personal care products dominated the observed mixture effects. The detected chemicals were not related to the observed genotoxicity. The large proportion of unknown toxicity calls for effect monitoring complementary to chemical monitoring.